The Use of Electronic Report Cards in The Merdeka Curriculum Within the Socrates School Information System - Anggraini, Catharina; Priyanti, Nita (Kirana Publisher (KNPub), 2025)
This research explores the implementation of the Electronic Report Card for the Independent Curriculum within the School Information System (SIS) Sokrates at TK Strada. The digital transformation of early childhood education requires a comprehensive approach to student development assessment and reporting. The study employs a descriptive qualitative method, collecting data through observation, interviews, and documentation across three Strada Kindergarten locations. Findings reveal the complexity of electronic report system implementation, with 40% of teachers experiencing initial adaptation difficulties and 70% facing technical challenges. Notably, 100% of respondents reported satisfaction with the system, indicating the success of SIS Sokrates design in meeting the pedagogical needs of the Independent Curriculum. The research uncovers that digital transformation is more than an administrative mechanism replacement, but a reconstruction of educational praxis positioning teachers as agents of change. The SIS Sokrates system successfully accommodates holistic assessment, facilitates individual development, and upholds the spirit of learning freedom. The research findings provide theoretical and practical contributions to developing an information technology-based assessment model responsive to contemporary educational needs.